Final answer:
The quadratic function f(x) = x² + 12x + 26 can be written in vertex form as f(x) = (x + 6)² + 2.
Step-by-step explanation:
The quadratic function given is f(x) = x² + 12x + 26. We can rewrite this function in vertex form by completing the square. First, we group the x terms and leave the constant term separate. Then, we take half of the coefficient of the x term, square it, and add it to both sides of the equation. Finally, we factor the quadratic expression and simplify to get the vertex form: f(x) = (x + 6)² + 2.